Rumen Microbial Protein Synthesis of Holstein Croossbred Heifer Fed King Grass, Corn Stover or Rice Straw as Basal Diet Supplemented with High Level of Protein Concentrate - Yulianti, A. (SEKOLAH PASCA SARJANA UGM, 2016)
Fifteen Dairy cattle of Holstein croossbred heifer were used for estimating Rumen microbial protein synthesis. The cattle fet by a diet of King Grass (KG), Corn Stover (CS) or Rice Straw (RS) ad libitum as basal diet that was supplemented by a high protein concentratin. Data obtained microbial protein synthesis (MPS) were analyzed using analyses of variance, in split plot and completely randomized design. The means defferences were analyzed by DMRT. The result of this research showed that purin derivatives concentration of cattle fed on KG, CS, and RS were 75.07; 67.72 and 61.86 m mol/day, respectively. The production of mivrobial protein synthesis values were respevtively 55.79, 49.43 g N/day and it was significantly defferent among diet (P<0.01). the Duncan test showed that KGs diet was the highest followed by CS’s diet and RS’s was the lowest.